OPTIMALISASI PEMANFAATAN LIMBAH PECAHAN BATA UNTUK MENINGKATKAN KETERAMPILAN BATU DI KELURAHAN NGADIRGO KOTA SEMARANG - Wicaksono, Teguh Mulyo; Wasino, Wasino; Mukhlisin, Muhammad; Supriyadi, Supriyadi; Sudarmono, Sudarmono; Junaidi, Junaidi; Sukoyo, Sukoyo; Suwarno, Anung; Mahmudi, Wildana Latif; Abdillah, Rifqi Aulia (Politeknik Negeri Semarang, 2024)
2022 is the beginning of offline learning after the Covid-19 pandemic. where previously learning was carried out online including practicums. One of the practicums carried out in the Semarang State Polytechnic Civil Engineering department is the masonry practicum which is carried out for semester 1 students. With the offline masonry practicum, the practicum will leave behind brick fragments that can no longer be used. These broken bricks will usually be thrown away at the end of each semester after all the practicums have been carried out. the proportion of brick fragments to intact bricks usually reaches 30% to 40%. The construction workers come from the Ngadirgo community, they learn building work autodidactically based on experience. With the continued development of BSB, there are quite a lot of employment opportunities, including development workers. Techniques and methods of masonry work that comply with construction standards can increase the ability of craftsmen to become skilled workers so that it is hoped that they can improve the welfare of the community around Ngadirgo sub-district, Mijen sub-district. Ngadirgo sub-district currently has a village cemetery which is located in Ngadirgo hamlet RW 2, in this cemetery there is no coffin house which is used to store death equipment including the coffin which is currently still entrusted to one of the residents' house. With the existence of coffin house products made from brick masonry in the village cemetery area.